NERACA FISIK PEMANFAATAN AREN DI KABUPATEN SIDRAP SULAWESI SELATAN: Physical Accounts for The Utilization of Sugar Palm in Lombo Village Pituriase District Sidrap Regency, South Sulawesi - Makkarennu Makkarennu; S Syahidah; Adelia Caroline; Igawati Alfari; M Misrawati; I Irnasari (Forestry Faculty of Universitas Hasanuddin, 2021)
Sugar palm is one of the leading committees widely used by the community as their source of income. The community uses and strives for this palm only relies on palm trees that grow naturally on their land in the forest. One of the constraints on the utilization of palm is the lack of information about the number of initial reserves to the final reserves of the utilization of natural resources. This Research was located in Lombo Village, Pitu Riase Subdistrict, Sidrap Regency, South Sulawesi Province. This study aims to calculate the final supply of raw materials of palm juice and palm sugar based on the number of palm trees owned by farmers. The collected data was done through observation and interviews with farmers involved in the palm sugar business as many as 32 people using census data collection. Data analysis is conducted by calculating initial inventory, addition, depletion (usage), and final supply of palm juice and palm sugar. The results showed that the final reserve amounts of raw materials sap as much as 6,183,799.3 liters. This condition indicates that the final reserves of palm sugar are sufficiently available for this region, with the use of palm juice amounting to 17.2% of the total initial inventory. The addition of stock palm trees can be done by replanting saplings to ensure the continuity of the palm sugar business.